2021
DOI: 10.1016/j.mayocpiqo.2021.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Thromboinflammatory Biomarkers in COVID-19: Systematic Review and Meta-analysis of 17,052 Patients

Abstract: Objective To evaluate differences in thrombo-inflammatory biomarkers between patients with severe COVID-19 infection/death and mild infection. Patients and Methods Medline, Cochrane Central Register of Controlled Trials, Embase, EBSCO, Web of Science, and CINAHL databases were searched for studies comparing thrombo-inflammatory biomarkers in COVID-19 among severe/non-survivors and non-severe/survivors from January 1, 2020 through July 11, 2020. Inclusion criteria: (1) h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
66
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 111 publications
6
66
0
4
Order By: Relevance
“…Similarly, a recent metanalysis reported higher D-Dimer levels in patients with a more severe form of the disease (WMD 0.60, 0.49–0.71, I 2 = 83.85%). Interestingly, this association seems to be independent from race and ethnicity 55 .…”
Section: Discussionmentioning
confidence: 86%
“…Similarly, a recent metanalysis reported higher D-Dimer levels in patients with a more severe form of the disease (WMD 0.60, 0.49–0.71, I 2 = 83.85%). Interestingly, this association seems to be independent from race and ethnicity 55 .…”
Section: Discussionmentioning
confidence: 86%
“…Interestingly, the high density of NETs formation containing microthrombi enriched of neutrophils and platelets found during COVID-19 is blocked by therapeutic dose of heparin [37]. Many other biomarkers have been described as associated with the severity of COVID-19 or the risk of thrombosis, such as inflammatory markers (e.g., interleukin-6) or hormonal markers [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Although we found no differences in gender, age or comorbidities between hospitalized versus outpatient management, a higher percentage of men 75%, required hospitalization compared with 57.8% of women; a point already observed for COVID-19 complications and viremia [8,18,19]. Additionally, 72% of patients with type 2 diabetes mellitus and 64.7% with hypertension were hospitalized.…”
Section: Discussionmentioning
confidence: 41%
“…Additionally, 72% of patients with type 2 diabetes mellitus and 64.7% with hypertension were hospitalized. These are commonly reported comorbidities in hospitalized COVID-19 patients [8,18,19]. Our analysis revealed that a low plasmatic level of HDL c and elevated Tg/HDL c ratio at the time of COVID-19 diagnosis is linked with requirement of hospitalization and illness severity as critical care patients showed the lowest HDL c concentration and highest Tg/HDL c ratio compared with severe and mild/asymptomatic COVID-19 patients.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation